Informational spillovers in the pre-1914 London Sovereign Debt Market - Marcelo de Paiva Abreu; Jo\~ao Manoel Pinho de Mello; Antônio de A. Sodré (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2007)
We document a novel type of international financial contagion whose driving force is shared financial intermediation. In the London peripheral sovereign debt market during pre-1914 period financial intermediation played a major informational role to investors, most likely because of the absence of international monitoring agencies and the substantial agency costs. Using two events of financial distress – the Brazilian Funding Loan of 1898 and the Greek Funding Loan of 1893 – as quasi-natural experiments, we document that, following the crises, the bond prices of countries with no meaningful economic links to the distressed countries, but shared the same financial intermediary, suffered a reduction relative to the rest of the market. This result is true for the mean, median and the whole distribution of bond prices, and robust to an extensive sensitivity analysis. We interpret this as evidence that the identity of the financial intermediary was informative, i.e, investors extracted information about the soundness of a debtor based on the performance of her financial intermediary. This spillover, informational in essence, arises as the flip-side of the relational lending coin: contagion arises for the same reason why relational finance (in this case, underwriting) helps alleviate informational and incentive problems,
Keywords: 330; Öffentliche Anleihe; Rentenmarkt; Großbritannien